Promotion the Dangers of Smoking in Adolescents at SMAN 8 Padang Sidempuan in 2022 - Siregar, Rahmah Juliani; Lisna Khairani Nasution; Elvi Suryani; Dewi Aminasty Siregar; Fatimah (IJCS: International Journal of Community Service, 2022)
Smoking is a habit of smoking cigarettes that is carried out in everyday life, is a necessity that cannot be avoided for people who have a tendency towards smoking. Cigarettes are one of the addictive substances that can lead to dependence for the wearer. The addictive nature of cigarettes comes from the nicotine they contain. After someone inhales cigarette smoke, within 7 seconds nicotine will reach the brain. All health experts including the World Health Organization (WHO) have long concluded that smoking has many negative health impacts, especially for children and their future. Cigarettes contain 4000 chemicals with 200 types of which are carcinogenic (can cause cancer), where these toxic materials are found in the main smoke, namely cigarette smoke which is inhaled directly into the smoker's lungs and side smoke, namely cigarette smoke produced by the tip of the cigarette that is burning, for example carbon monoxide, benzopyrene, and ammonia. This PKM activity aims to increase the knowledge of teenagers at SMA N 8 Padangsidimpuan about the dangers of smoking by providing education related to efforts to increase knowledge about MKJP. The method used in carrying out this activity is through lectures and discussions. The results of this PKM activity aim to increase knowledge by providing Communication, Information and Education (IEC) with good KIE there will be a communication process with the dissemination of information that accelerates behavior change from the community.